2006
DOI: 10.1136/bjo.2006.103556
|View full text |Cite
|
Sign up to set email alerts
|

3-day treatment with azithromycin 1.5% eye drops versus 7-day treatment with tobramycin 0.3% for purulent bacterial conjunctivitis: multicentre, randomised and controlled trial in adults and children

Abstract: Azithromycin 1.5% for 3 days was as effective and as safe as tobramycin for 7 days. Furthermore, more azithromycin than tobramycin patients presented an early clinical cure at Day 3. Due to its twice daily dosing regimen for 3 days, azithromycin represents a step forward in the management of purulent bacterial conjunctivitis, especially in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…On day 9, the clinical cure rate of more than 80% was similar to those described in the overall population of this study 34 as well as those reported in the literature in children: 80% to 90%. 3,4,11 These levels even quite similar, were statistically different by bootstrap method (81.8% for tobramycin group versus 80% for azithromycin; P Ͻ 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…On day 9, the clinical cure rate of more than 80% was similar to those described in the overall population of this study 34 as well as those reported in the literature in children: 80% to 90%. 3,4,11 These levels even quite similar, were statistically different by bootstrap method (81.8% for tobramycin group versus 80% for azithromycin; P Ͻ 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…It binds reversibly to the 50S subunit of the bacterial ribosome and inhibits RNAdependent protein synthe (13) . Azithromycin was studied in bacterial conjunctivitis and proved to be both effective and safe with good patient tolerance (14,15) . The purpose of the present study is to determine the efficacy of topical azithromycin 1.5% ophthalmic solution combined with eye lid hygiene in the treatment of patients with moderate to severe anterior and/or posterior blepharitis and to compare two different modalities of administration: a threeday regimen versus a prolonged onemonth regimen.…”
Section: Introductionmentioning
confidence: 99%
“…The problem arose in a few cases in the daily dosing schedule of Tobramycin 0.3%, Ofloxacin 0.3% and Gatifloxacin 0.3% when used in the postoperative setting. Two cases out of twelve who were administered Tobramycin and one out of six administered Ofloxacin were using the drug twice a day instead of the standard regimen of six hourly administration 13 . One person was incorrectly administered Gatifloxacin three times a day against the standard regimen of six hourly dosing 14 .…”
Section: Discussionmentioning
confidence: 99%